Scaling‐up HCV prevention and treatment interventions in rural United States—model projections for tackling an increasing epidemic. (20th September 2017) - Fraser, Hannah; Zibbell, Jon; Hoerger, Thomas; Hariri, Susan; Vellozzi, Claudia; Martin, Natasha K.; Kral, Alex H.; Hickman, Matthew; Ward, John W.; Vickerman, Peter
Abstract: Background and aims: Effective strategies are needed to address dramatic increases in hepatitis C virus (HCV) infection among people who inject drugs (PWID) in rural settings of the United States. We determined the required scale‐up of HCV treatment with or without scale‐up of HCV prevention interventions to achieve a 90% reduction in HCV chronic prevalence or incidence by 2025 and 2030 in a rural US setting. Design: An ordinary differential equation model of HCV transmission calibrated to HCV epidemiological data obtained primarily from an HIV outbreak investigation in Indiana. Setting: Scott County, Indiana (population 24 181), USA, a rural setting with negligible baseline interventions, increasing HCV epidemic since 2010, and 55.3% chronic HCV prevalence among PWID in 2015. Participants: PWID. Measurements: Required annual HCV treatments per 1000 PWID (and initial annual percentage of infections treated) to achieve a 90% reduction in HCV chronic prevalence or incidence by 2025/30, either with or without scaling‐up syringe service programmes (SSPs) and medication‐assisted treatment (MAT) to 50% coverage. Sensitivity analyses considered whether this impact could be achieved without re‐treatment of re‐infections, and whether greater intervention scale‐up was required due to the increasing epidemic in this setting. Findings: To achieve a 90% reduction in incidence and prevalence by 2030, without MAT and SSP scale‐up, 159 per 1000 PWID (initially 24.9% of infected PWID) need to be HCV‐treated annually. However, with MAT and SSP scaled‐up, treatment rates are halved (89 per 1000 annually or 14.5%). To reach the same target by 2025 with MAT and SSP scaled‐up, 121 per 1000 PWID (19.9%) need treatment annually. These treatment requirements are threefold higher than if the epidemic was stable, and the impact targets are unattainable without retreatment. Conclusions: Combined scale‐up of hepatitis C virus treatment and prevention interventions is needed to decrease the increasing burden of hepatitis C virus incidence and prevalence in rural Indiana, USA, by 90% by 2025/30.